New Coronavirus pandemic and the functioning of dental services in Brazil: a four-month follow-up (Research, Society and Development, 2021)
Objective: The present study analyzed the closure and opening of elective dental services in response to Covid-19 and moving average of the epidemic curve of four Brazilian states, Amazonas, Ceará, São Paulo, Santa Catarina and Federal District, in addition to the position of the Federal and Regional Council of Dentistry. Method: This was a study of five cases based on the analysis of secondary and documentary data from publications of the Federal and Regional Council of Dentistry with follow-up from March to June 2020. The mobile average of new cases and daily deaths by Covid-19 per state was calculated. Results: The suspension of services occurred in the second half of March in all states. The reopening of elective dental services did not comply with any epidemic trend criteria, and varied in the states studied between April and June. Conclusion: The reopening of the services did not comply with any criteria of trend of the epidemiological curve of the number of cases and deaths and the occupancy rate of ICU beds, and there is no clarity of state documents on enforcement mechanisms and fine for services that fail to meet the standards, aspects that compromise the safety of professionals and users of services, especially by the use of aerosols.